2017
DOI: 10.1902/jop.2016.160353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Dexamethasone and Ibuprofen for Postoperative Pain Prevention and Control After Surgical Implant Placement: A Double‐Masked, Parallel‐Group, Placebo‐Controlled Randomized Clinical Trial

Abstract: Steroidal dexamethasone is as effective as non-steroidal ibuprofen for preventing or controlling postoperative pain and discomfort after surgical implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 33 publications
1
45
0
1
Order By: Relevance
“…The following were excluded: pregnant or lactating women, use of some type of medication that could affect the perception of pain, history of allergy or intolerance to the drugs (ibuprofen and paracetamol) used in the research; and history of alcohol or drug abuse. -Sample Calculation Using statistical power analysis software R (software, R Foundation, Vienna, Austria), it was determined that 25 patients per group would be required to achieve 80% of power at 95% of confidence interval (CI), assuming moderate to intense changes in pain score 24 hours after surgery in at least one group and non-normal distribution data (16). In order to compensate for possible data loss during the study, the number of individuals allocated per group was increased by 10%, with 27 patients per group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following were excluded: pregnant or lactating women, use of some type of medication that could affect the perception of pain, history of allergy or intolerance to the drugs (ibuprofen and paracetamol) used in the research; and history of alcohol or drug abuse. -Sample Calculation Using statistical power analysis software R (software, R Foundation, Vienna, Austria), it was determined that 25 patients per group would be required to achieve 80% of power at 95% of confidence interval (CI), assuming moderate to intense changes in pain score 24 hours after surgery in at least one group and non-normal distribution data (16). In order to compensate for possible data loss during the study, the number of individuals allocated per group was increased by 10%, with 27 patients per group.…”
Section: Methodsmentioning
confidence: 99%
“…Three classes of analgesic drugs [blockages with local anesthetics, non-steroidal anti-inflammatory drugs (NSAIDs) and opioids] have been used for this purpose alone or in combination (5,6). Several studies have been conducted in PA, particularly in third molar extraction surgeries (7-12,) periodontal surgeries (13)(14)(15), and few studies in implant dentistry (1,(16)(17)(18), with conflicting results. In addition, different types of drugs have been tested in PA (1,9,(13)(14)(15)(16) however without a consensual definition of the best protocol regarding the drug, posology and period of exposure to the drug.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dexamethasone has been reported to inhibit peripheral phospholipase, which decreases the pain-aggravating agents from the cyclooxygenase and lipoxygenase pathways. [7] Previous studies have shown the analgesic effect of dexamethasone in general and orthopedic surgery. In addition, preoperative administration of dexamethasone has been reported to reduce postoperative nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%